Implementation of innovation and project management best practices in technological development. Case study: natural antioxidants from olive pomace in the main olivegrowing area of Argentina - Renzi, L. (2025)
Fil: Renzi, L. Instituto Nacional de Tecnología Industrial. Sede San Juan (INTI-San Juan); Argentina